Konstruksi Daya Saing Kartu E-Toll Bank Mandiri dari Perspekrif Pelanggan dengan Implementasi Model Technology Acceptance Model (TAM) - Atika Rahmayanti; Martani Husaeni (Sekolah Pascasarjana Perbanas Jakarta, 2017)
The purpose of this research is to find out and analyze the influence of model Technology Acceptence of Model (TAM) on the e-Toll card. This type of research is descriptive and causal research in methods of survey. Sampling techniques using a purposive sampling techniques as well as the analysis of Structural Equation Models (SEM). The result showed that only the variables that influence significantly and positive to PEU variable ATB, as for the other exogenous have an effect that is not significantly to endogen variables because the value of the probability is greater than 5% alpha. In addition, the only variable PU against BIU value is positive, while the estimate for other exogenous variables influence negatively to endogen because the value of estimate variable negative. Based on the results of the study authors advise that Bank Mandiri consumer complaints handling need to perform effectively and provide a high level of service compared to other competitors who publish e-Payment so that consumers are more interested in using e-Toll than using cash payment system because consumers get satisfaction product for the use of e-Toll